Culture and global societal threats: COVID-19 as a pathogen threat to humanity. (February 2021) - Kashima, Yoshihisa; Dennis, Simon; Perfors, Andrew; Laham, Simon M.
The COVID-19 global pandemic has brought into sharp focus the urgency of tackling the question of how globalized humanity responds to a global societal threat, which can adversely affect a large portion of the human population. Changing geospatial distribution of COVID-19 morbidity paints a gloomy picture of cross-national differences in human vulnerabilities across the globe. We describe the dynamic nexus among societal – particularly pathogen – threat, social institutions, and culture, and discuss collectivism (ingroup favouritism and outgroup avoidance) and tightness (narrow prescription of behaviours and severe punishment of norm violations) as potential cultural adaptations to prevalent pathogen threats. We then sketch out a theoretical framework for cultural dynamics of collective adaptation to pathogen threats, outline a large number of theory- and policy-relevant research questions and what answers we have at present, and end with a call for renewed efforts to investigate collective human responses to societal threats.